Problematic of the Metaphysics of Aristotle in the Light of the «ἐνέργεια» - Villodres Maldonado, David (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2021)
We approach the problem about the meaning of Aristotle's Metaphysics from a perspective that, beyond the historiographic and hermeneutical approach of contemporary Aristotelianism, seeks its foundation in the very analytic-modal nature of the first philosophy centered on the concept of ἐνέργεια. Based on this approach, we discard that the text entitled «Metaphysics», whose authorship is attributed to Andrónico de Rodas, is an exposition of Aristotle's first philosopher, defending a new configuration of it in which the metaphysical and logical treatises, published in the corpus Aristotelicum separately, are integral moments of it.